Low level wind shear over Bomba airport - KUMAR, SURENDRA; PATKAR, P.V. (MAUSAM, 1993)
Significant climatological features based on 329 Low Level Wind Shear (LLWS) reports from 1985 to 1989 at Bombay airport are presented, The monsoon season has the highest frequency of occurrence of LLWS mainly due to thunderstorms and strong gusty winds, Other than monsoon season, occurrence of LLWS is related to sea and land breeze and nocturnal increase of surface temperature during night. The preferred time of occurrence of LLWS is between 0000 to 0600 IST and 1800 to 240J IST. The simultaneous occurrence of strong and severe LL WS, low cloud ceiling and very poor visibility has an adverse effect on aircraft operations at Bombay airport during landing and take-off.